Nursing Integration and Innovation Across a Multisystem Enterprise: Priorities for Nurse Leaders. Issue 1 (January 2018) - Pappas, Sharon; McCauley, Linda
Abstract : There is no escaping the fact that the ability to skillfully influence change is a requirement for nurse leaders. This need is intensified as the national health care system reforms and as the morphology of health care systems continues to change, especially in academic health care systems. The purpose of this article was 2-fold. The first objective was to relay the experience of the integration of nursing practice, education, and research within an academic health care system. The second was to, through this story of integration, expose the uniqueness and importance of nurse leader roles influencing innovation across a multisystem enterprise to fulfill the organization's mission.